Metode Trial And Error Dalam Pembelajaran Tahsinul Al-Qur’an - Rafiqa Noviyani (Ikhtisar: Jurnal Pengetahuan Islam, 2023)
The purpose of this study is to describe the process of trial and error method in learning tahsinul Qur'an. The method of trial and error or known as the Throndike theory was proposed by Edward Lee Throndike, a behavioristic scientist. The basic principle of trial and error is the existence of a stimulus-forming relationship of messages that will be conveyed through attitudinal responses formed from the law of readiness, the law of effect, the law of practice and the law of attitude. So it takes a continuous repetitive process. In learning tahsinul Qur'an, the process of repeating greatly determines the results of learning outcomes. The main purpose of tahsinul Qur'an is to achieve the ability to read and memorize the Qur'an according to the rules of makharijul letters and the law of tajweed. The achievement of the concept of learning tahsinul Qur'an based on trial and error methods requires data analysis in the form of books, journals and other supporting theories through library research. The results of library research on the trial and error method in learning tahsinul qur'an are through the 4T process, namely Tahsinul makharijul letters and harakot, Talqin tajweed laws word for word to get consistency in the sound of tajweed law, Tajribah to get the results of reading Qur'anic verses according to the makharijul letters and consistent tajweed laws and Ta'lif-Lafdzi as the final response to achieving the process of repetition through writing and pronunciation.